Building Harmony and Reducing the Potential for Conflict Through Religious Moderation - Jupri Jupri; Siti Ropiah; Thobi’in Thobi’in; Nasori Nasori (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The main objective of this study is to understand to what extent the values of religious moderation such as tolerance, balance, justice, and respect for diversity can strengthen social relations and prevent the emergence of religion-based conflicts in Indonesia’s plural society. This study examines how the implementation of religious moderation can play a role in fostering interreligious harmony and reducing the potential for social conflict within a pluralistic society. The method used is qualitative research with a descriptive approach, conducted through literature studies, interviews with religious leaders, and observations of interfaith activities in several regions with high levels of diversity. The results show that the practice of religious moderation, implemented through education, interfaith dialogue, and the active involvement of religious figures and institutions, has proven effective in strengthening mutual trust among religious communities. The values of religious moderation also contribute to building collective awareness to reject violence, prioritize deliberation, and uphold humanity above differences in belief. This study concludes that religious moderation is an effective approach to building harmony and preventing social conflict. Through the application of moderation values, society can live together peacefully, appreciate diversity, and reinforce social and national integration. The implications of this research emphasize the importance of strengthening religious moderation programs through public policy, character education, and interfaith social activities. The government, religious institutions, and society need to work together to instill the values of moderation as the main foundation for creating a harmonious and just national life.